PEMBINAAN KESISWAAN DI SEKOLAH MENENGAH PERTAMA NEGERI KECAMATAN SUNGAYANG KEBUPATEN TANAH DATAR - Oscar Gare Fufindo (Jurnal Bahana Manajemen Pendidikan, 2013)
The purpose of this research is to know the information about student development at Junior High School Sub district Sungayang District Tanah Datar. The population are 364 students and the sample are 55 students those are taken random by using simple random sampling technique. The instrumen of this research is opened quesioner that had construck validity testing. Data analized use percentage formula. The result of this research explain that the school had done student development by some student activities. Kata kunci: student development